2017
DOI: 10.1016/j.juro.2017.06.086
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of PD-1 and PD-L1 Expression in Patients with High Grade Upper Tract Urothelial Carcinoma

Abstract: PD-1 positivity of tumor-infiltrating lymphocytes was associated with adverse pathological criteria and independent prognostication of worse survival outcomes. PD-L1 positivity of tumor cells was an independent prognosticator of favorable survival outcomes in cases of organ confined disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 30 publications
7
47
0
Order By: Relevance
“…Skala et al did not detect a correlation between PD‐L1 positivity and cancer‐specific survival, while Zhang et al reported that PD‐L1 positivity on tumor cells was associated with poor cancer‐specific survival. In contrast, Krabbe et al reported that PD‐L1 positivity was associated with better outcomes among patients with high‐grade organ‐confined UTUC. There are several possible explanations for these discrepancies, such as differences in the cohorts and immunohistochemical methods (eg, antibody clones, detection systems, and positivity cutoffs).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Skala et al did not detect a correlation between PD‐L1 positivity and cancer‐specific survival, while Zhang et al reported that PD‐L1 positivity on tumor cells was associated with poor cancer‐specific survival. In contrast, Krabbe et al reported that PD‐L1 positivity was associated with better outcomes among patients with high‐grade organ‐confined UTUC. There are several possible explanations for these discrepancies, such as differences in the cohorts and immunohistochemical methods (eg, antibody clones, detection systems, and positivity cutoffs).…”
Section: Discussionmentioning
confidence: 90%
“…First, the immunohistochemistry was performed using TMA slides, rather than whole‐tissue sections, which may have resulted in underestimated heterogeneity of the tumors’ PD‐L1 positivity. However, TMAs are useful for examining large numbers of samples in standardized conditions and are widely used in studies that have examined PD‐L1 positivity in various cancers . In addition, we systematically constructed the TMAs using large 2‐mm cores from the tumor's center and periphery and detected a significant correlation between PD‐L1 positivity at the two regions in the same tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD‐L1 expression in TCs impairs T‐cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape . In several cancer types, such as HNSCC, oropharyngeal squamous cell carcinoma (SCC), pulmonary adenocarcinoma, oesophageal SCC, and urothelial carcinoma, PD‐L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al .…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] In the present study, we investigated the immune environment in SDC, which is an an aggressive high-grade salivary malignancy, focusing on the immunoexpression of PD-L1, PD-1, the CTA PRAME, and MHC I. PD-L1 expression in TCs impairs T-cell regulation, disrupts the antitumoral immune response, and contributes to an immunosuppressive microenvironment, allowing tumour immune escape. 1,[33][34][35][36] In several cancer types, such as HNSCC, 12 oropharyngeal squamous cell carcinoma (SCC), 37 pulmonary adenocarcinoma, 38 oesophageal SCC, 39 and urothelial carcinoma, 40 PD-L1 immunoexpression has been reported to be associated with advanced tumour stage, poor clinical outcome, and/or decreased overall survival. Similarly, in a cohort of 219 salivary gland carcinomas of various types, including 31 SDCs, Mukaigawa et al reported that a high level of PD-L1 expression in TCs was associated with poor overall survival, DSS, and DFS.…”
Section: Discussionmentioning
confidence: 99%